Patient-Specific Instrumentation in Total Knee Arthroplasty: A Review - Nam, Denis; McArthur, Benjamin A.; Cross, Michael B.; Pearle, Andrew D.; Mayman, David J.; Haas, Steven B. (The Journal of Knee Surgery, 2012)
Recently, patient-specific approaches to total knee arthroplasty (TKA) have been introduced, in which preoperative imaging (plain radiographs, computed tomography, and magnetic resonance imaging) are used to manufacture cutting blocks specific to a patient's anatomy. Proposed benefits of patient-matched cutting blocks include a decrease in operative time, instrument trays required, and the ability to preoperatively plan a patient's component size, position, and alignment. In addition, an improvement in postoperative mechanical alignment is expected, without violation of the intramedullary canal. However, questions remain regarding patient outcomes and the cost-effectiveness associated with patient-specific cutting block technology. This article will review the evolution of surgical techniques in TKA, the development of patient-specific cutting blocks, surgical considerations, and the literature associated with this new technology.
Keywords: total knee arthroplasty; patient-specific instrumentation; alignment; cost-effectiveness